MEDIA AUDIOVISUAL TERHADAP PEMAHAMAN BUNYI DALAM BINA KOMUNIKASI PERSEPSI BUNYI DAN IRAMA BAGI SISWA KELAS 1 - Tri Wulandari, Evi (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Hearing impairment experienced by the children had impact to the disorder of speaking development so that it prevented the development of social interaction, information acquisition, communication, and intelligence. Therefore, the development of speaking skill for the children had to be done soon in order that it did not prevent the ability development above. Developing speaking ability was done through the program of communication guide, sound and rhythm perception. Learning this program should look at the student’s characteristics which was sensitive toward the visual ability. Therefore it was applied audiovisual media in implementing the program. This media was the integration between visual (picture and movement) and audio (sound). This research had purpose to describe whether there was influence of audiovisual media toward sound understanding in the program of communication guide, sound and rhythm perception to hearing impairment students of class 1 in SLB-B Karya Mulia 1 Surabaya or not. This research used quantitative approach with pre experiment arrangement, one-group pretest-posttest design. The independent variable was audiovisual media and the dependent variable was sound understanding to the program of communication guide, sound and rhythm perception. This research target was hearing impairment students of class 1 in SLB-B Karya Mulia 1 Surabaya numbering 6 students. The data collection method used writing test (doing multiple choice exercise and short explanation), the data analysis used sign test. The research result indicated that there was average value enhancement of understanding sound ability i.e. pre test was 42,33 and post test was 83,83. Z table 5% to two sides examinationwas 1,96 and Zh obtained was 2,05 so that null hypothesis was refused and work hypothesis was accepted. Based on the explanation above, it could be concluded that there was significant influence of using audiovisual media toward sound understanding toward the program of communication guide, sound and rhythm perception to hearing impairment students in SLB-B Karya Mulia 1 Surabaya.   Keywords: Audiovisual Media, Sound Understanding